A Muscle Physiology-Based Framework for Quantifying Training Load in Resistance Exercises - Frank Imbach; Stéphane Perrey; Thomas Brioche; Robin Candau (Sports)
Background: Objective training load (TL) indexes used in resistance training lack physiological significance. This study was aimed to provide a muscle physiology-based approach for quantifying TL in resistance exercises (REs). Methods: Following individual torque–velocity profiling, fifteen participants (11 healthy males, stature: 178.36 ± 3.95 cm, and body mass (BM): 77.48 ± 7.74 kg; 4 healthy females, stature: 169.25 ± 5.03 cm, and body mass: 60.62 ± 3.91 kg) performed isokinetic leg extension exercise sessions at low, moderate, and high intensities (LI, MI, and HI, respectively). Systemic and local physiological responses were measured, and sessions were volume-equated according to the “volume-load” (VL) method. Results: Significant differences were found between sessions in terms of mechanical work (<semantics>p<0.05</semantics> and <semantics>p<0.001</semantics>, for LI-MI and MI-HI, respectively), averaged normalised torque (<semantics>p<0.001</semantics>), mechanical impulse (<semantics>p<0.001</semantics>), and rate of force development (RFD, <semantics>p<0.001</semantics> for LI-MI). RFD was mainly impacted by the accumulation of repetitions. Muscle function impairments mainly occurred at low intensities–long series, and high intensities, supported by greater RFD rate decay and changes in electromyographic activity. Therefore, accounting for muscle fatigue kinetics within objective TL indexes and using dimension reduction methods better described physiological responses to RE. Conclusions: A generic equation of muscle fatigue rise could add value to TL quantification in RE. Considering other training-related information and TL indexes stands essential, applicable to field situations and supports the multidimensional facet of physiological responses to RE.